Sādha saṅgraha Rādhāsvāmī : athavā, Rādhāsvāmī mata kī bhaktamāla : jisameṃ Svāmījī Mahārāja, Huzūra Mahārāja, Mahārāja Sāhaba, Buājī Sāhabā, aura Bābūjī Mahārāja ke samaya ke 60 bhaktoṃ kī jīvaniyāṃ likhī gaī haiṃ - Maheshwari, S. D. (Māheśvarī, 1964)
Hagiographical narratives about some exponents and followers of the Council Group of the Radhasoami Satsang, Hindu sect.